A Comprehensive Test Approach on High-Power Low-Noise Intermodulation Distortion - Lei Wang; Jingyi Zhang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
With the shortage of wireless communication bandwidth resource, the radio interferences occur so frequently. Currently, effcient frequency allocation algorithm designing and Intermoduation Distortion (IMD) suppression are two means to rationally improve the bandwidth resource. Therefore, four comprehensive approaches named stimulus isolation, channel crosstalk isolation; spectrum slight offset and Auto Level Control (ALC) leak control are proposed respectively to avoid the restriction of the periphery system’s noise and dynamic range of measurement instruments. Moreover, the high power and low noise detection approach, the auxiliary components amelioration and the measurement system improvement are analyzed. Finally, utilizing Silicon-On-Insulator (SOI) Radio Frequency (RF) switch as the carrier to do the experiment based on Advantest 93K tester. Experiment results show that the comprehensive optimized approaches can keep the whole system to less than -150 dBm (nearly 170 dBc) low noise range under the large signal cases. The actual intermodulation distortion signal could be rejected and sampled in precise accuracy which is nearly 20% improved. What’s more, the approaches are also beneficial to the expansion of the industrial multi-site test.